Venezuela's Crisis: A Multifaceted Examination of Economic, Political, and Humanitarian Challenges - Gonzalo Da Silva (International Journal of Science and Society, 2023)
Venezuela's ongoing crisis has garnered international attention and concern due to its multifaceted nature. This article delves into the complex web of economic, political, and humanitarian challenges that have plagued the South American nation in recent years. It aims to provide an in-depth analysis of the factors contributing to Venezuela's crisis and its impact on both the country's population and the global community. The economic mismanagement, political turmoil, and humanitarian suffering in Venezuela have created a crisis with far-reaching implications for regional stability and international relations. This article underscores the urgency of finding a sustainable solution to Venezuela's crisis to alleviate the suffering of its citizens and restore stability to the nation, emphasizing the importance of international cooperation and diplomatic efforts in this endeavor.